A SIMULATED REDUCTION IN ANTARCTIC SEA-ICE AREA SINCE 1750: IMPLICATIONS OF THE LONG MEMORY OF THE OCEAN - Goosse, H.; Renssen, H. (International Journal of Climatology, 2005)
Using the three-dimensional coarse-resolution climate model ECBILT-CLIO, 1000-year long ensemble simulations with natural and anthropogenic forcings have been performed to study the long-term variation of the ice cover in the Southern Ocean. Over the last 250 years, the ice area has decreased by about 1 × 10